If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 4) + -3 = 12 Reorder the terms: 5(4 + x) + -3 = 12 (4 * 5 + x * 5) + -3 = 12 (20 + 5x) + -3 = 12 Reorder the terms: 20 + -3 + 5x = 12 Combine like terms: 20 + -3 = 17 17 + 5x = 12 Solving 17 + 5x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + 5x = 12 + -17 Combine like terms: 17 + -17 = 0 0 + 5x = 12 + -17 5x = 12 + -17 Combine like terms: 12 + -17 = -5 5x = -5 Divide each side by '5'. x = -1 Simplifying x = -1
| -3=3-3(2t-1) | | 4x+3+2x-5=7x-8 | | 1-8v=-56v | | 8.2p=32.8 | | .7x-0.3=.6x+5 | | 2b+14=10 | | W=8(3.14)b | | 3x+10+6x+7=180 | | 4x+3xy+4y^2=25 | | 4+x/2-3=-7 | | 2(5-5x)=15.1-7x | | 2(5-10x)=15.1-7x | | 2p-3=6-p | | 8x+1+11x-1=19 | | F(x)=-x^3+8x^2+3 | | .04x+.07(10000-x)= | | -5a+54=5(-49+13.89) | | 2(5-9x)=15.1-7x | | X=90x+35 | | 29x+33-14x=162 | | (3v-7)(4+v)=0 | | 20j+2m=480 | | F(x)=-x^3+8x^2+3f(-7) | | 3w^2+4w+10=0 | | -1.4d=.7 | | 2x+8-4(x+1)=7x+9 | | 2(4+x)=10-5x | | 2x-y=97 | | 2h+0.2=4h+.2 | | x+10=5x-40 | | 3x^2+0x+3y^2+5y+0=0 | | 2x-8+3x+1=-7 |